The elements of culture values on malay traditional food wrapping : ketupat / Mhd Nor Osman, Norhasandi Mat and Mohd Khairul Azahari Abdul Rani - Mhd Nor, Osman; Norhasandi, Mat; Mohd Khairul Azahari, Abdul Rani (Universiti Teknologi MARA, Perak, 2016)
Most of the traditional food wrapping is made from various natural materials. Ketupat is one of the traditional foods in Malaysia and in the Malay Archipelago. It is wrapped coconut leaves called janur The origin of the Ketupat or Kupat is from Java, Indonesia. The migration of peoples in the Malay Archipelago has made the Ketupat with many similarities in terms of its use. The tradition of making the Ketupat started a few generations ago and became mandatory in certain ceremonies as a main meal. This activity is considered as a culture since it has been passed down through generations and has become a symbol to identify the community. Ketupat requires technical skills to weave Its container, besides have its physical attractive characteristics and significant aesthetic values in shapes, lines, patterns and colors. Ketupat also has different symbolic meanings and has become beliefs in daily life. The effect of modern packaging has hit the tradition and threatens the art of weaving the Ketupat. Therefore, although we are in the mainstream of development but we must preserve the elements of culture values on Malay traditional food wrapping (Ketupat).